Dried distillers grains with solubels as effective replacement of soybean meal in Boer goat diets - McAtee, Taylor B.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Dried distillers grains with solubles (DDGS) may be an effective replacement of soybean meal (SBM) in boer goat diets. The global goat population is growing and DDGS could be a cost effective alternative. With the per protein unit cost advantage of DDGS over SBM being $1.86, DDGS would price into goat diets as a protein source (October 26, 2017 U.S. Grains Council Report). There has been no peer reviewed research done on DDGS in Boer goat diets. The objective of this experiment was to evaluate the efficacy of DDGS as a replacement of SBM in Boer goat diet. Forty-eight meat goat kids (approximately 70 d of age) were used in a completely randomized design. There were 3 kids per pen (4 pens per treatment). Kids were allotted into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All diets were pelleted containing roughage, so no supplemental forage was needed. Diets were fed for 47 days, with ADG, ADFI, and G:F calculated every 2 weeks. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pen serving as the experimental unit. The model included effects DDGS level with P-value ≤ 0.05 considered significant. LS Means was utilized to partition treatment differences (P < 0.05). We observed an overall treatment effect (P <.001) of G:F from day 0-47. Overall treatments had no effect (P <.05) on ADG, BW, HCW, Carcass Yield.In conclusion, DDGS did not have an overall treatment effect on ADG, HCW, or Carcass yield. Feed efficiency improved equally with the addition of DDGS to the diet of treatments 66% and 100% SBM inclusion of DDGS, while treatments 0% and 33% SBM feed efficiency were lower but also equal. There were relatively no differences whether fed DDGS or SBM, with a minor improvement of feed efficiency with DDGS. These findings suggest that DDGS are an effective replacement of soybean meal in Boer goat diets with inclusion levels of 66% or 100%.
Keywords: Spring 2018